1990
DOI: 10.1111/j.1365-2826.1990.tb00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Vasopressin from the Septum and Hippocampus of Freely Behaving Male Rats: Effect of Bacitracin and Synthetic Vasopressin

Abstract: This paper describes the release characteristics of arginine vasopressin (AVP) from the dorsal septum and dorsal hippocampus of freely behaving male rats using miniaturized push-pull cannulae and a slow rate of perfusion to minimize tissue damage. The major findings were that: 1) The spontaneous release of immunoreactive AVP (I-AVP) from the dorsal hippocampus was episodic in nature and did not require the presence of bacitracin in the perfusion medium to reliably demonstrate its pattern of release; 2) despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…First, it appears to be site-specific within the septum since perfusion of the dorsal region of the septum and not the ventral septum led to increases in I-AVP release as shown in the preceeding paper (8). Secondly, the positive feedback action of AVP is dose-dependent and it tends to saturate at high doses.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…First, it appears to be site-specific within the septum since perfusion of the dorsal region of the septum and not the ventral septum led to increases in I-AVP release as shown in the preceeding paper (8). Secondly, the positive feedback action of AVP is dose-dependent and it tends to saturate at high doses.…”
Section: Discussionmentioning
confidence: 91%
“…In the previous paper (8) it was shown that to measure detectable levels of immunoreactive AVP (I-AVP) from the septum of freely behaving male rats the superfusion medium had to contain effective concentrations of bacitracin, an aminopeptidase inhibitor. Therefore, in these in vitro experiments we first studied the spontaneous release of I-AVP from septal fragments in the Presence of different concentrations of bacitracin in the perfusion medium as well as the response of the tissue to a pulse of synthetic AVP infused for 5 min.…”
Section: Resu Itsmentioning
confidence: 99%
See 3 more Smart Citations